Determination of mosquitoes species diversity and molecular detection of West Nile virus in wild bird habitats in Perak and Selangor, Malaysia - Jafar Ali, Natasha (2022)
West Nile virus (WNV) is a zoonotic and emerging arthropod-borne RNA virus from the Flaviviridae family. The virus is maintained in a sylvatic cycle between vectors and reservoirs host, the wild birds. Mosquitoes, especially Culex spp, acquired WNV from wild birds and transmitted it into the susceptible dead-end hosts such as humans and other mammals. Previous discovery of Kunjin virus, a subtype of WNV in mosquitoes from Malaysia, was more than half a century ago. Meanwhile, WNV antibodies and/or RNA have been demonstrated in wild birds, human, wildlife such as macaques and bats; and farm animals such as swine and horse from 2003 until now. Presence and transmission of WNV in these species certainly involved mosquito vectors, yet the study on the current status of WNV in mosquitoes is lacking, which further signifies the need of this study. The aim of this study was identifying the diversity of mosquito species found near to the wild bird habitats and determining the presence of WNV RNA in the mosquitoes in the selected areas of West Coast Malaysia. Mosquitoes were trapped by using CDC Light Trap baited with carbon dioxide followed by sex and species identification with morphological and taxonomic keys under stereomicroscope. The mosquitoes were pooled into 10 based on sex, species, and collection site. Subsequently, nested RT-PCR targeting conserved region between the capsid and the pre-membrane gene of WNV was conducted to detect WNV RNA. Positive amplicon from nested RT-PCR assay was further analysed using partial sequencing analysis. Overall, 2635 mosquitoes were collected from Kuala Gula Bird Sanctuary, Perak (1417 mosquitoes) at percentage of 53.78 and Kapar Energy Venture, Selangor (1218 mosquitoes) at percentage of 46.22. Nested RT-PCR revealed that WNV RNA was detected from 35 out of 285 (12.28%) mosquito pools, which belongs to six different species namely Culex tritaeniorhynchus (24 pools), Culex vishnui (6 pools), 2 pools of Culex pseudovishnui, 1 pool of Culex gelidus, 1 pool of Armigeres subalbatus and 1 pool of Coquillettidia spp. Minimum infection rate (MIR) presenting the highest value on Culex tritaeniorhynchus which was 9.11. Partial sequencing analysis revealed that the isolates share 90.12- 97.01% similarity with the isolates found in Malaysia, Africa, Germany, Romania, Italy and Israel. Phylogenetic analysis signifies that isolates from this study is grouped in lineage 2. In conclusion, Culex species are the most significant species infected with WNV collected in this study suggesting that WNV is circulating among the mosquitoes in Malaysia. The MIR value on this species indicates high possible risk of WNV transmission in this study. Evidence of WNV in the mosquitoes further substantiate the need of enhancing vector control program and continuous surveillance of WNV in the reservoir, vector and susceptible host.